Phylogeny of frogs from the genus Physalaemus (Anura, Leptodactylidae) inferred from mitochondrial and nuclear gene sequences - Lourenco, Luciana B.; Targueta, Cintia P.; Baldo, Diego; Nascimento, Juliana; Garcia, Paulo C. A.; Andrade, Gilda V.; Haddad, Celio F. B. [UNESP]; Recco-Pimentel, Shirlei M. (Elsevier B.V., 2015)
Although some species groups have been recognized in the leiuperine genus Physalaemus, no phylogenetic analysis has previously been performed. Here, we provide a phylogenetic study based on mitochondrial and nuclear DNA sequences from 41 of the 46 species of Physalaemus. We employed the parsimony criterion using the software TNT and POY and the Bayesian criterion using the software MrBayes. Two major clades were recovered inside the monophyletic Physalaemus: (i) the highly supported Physalaemus signifer Clade, which included P. nattereri and the species previously placed in the P. deimaticus and P. signifer Groups; and (ii) the Physalaemus cuvieri Clade, which included the remaining species of Physalaemus. Five species groups were recognized in the P. cuvieri Clade: the P. biligonigerus Group, the P. cuvieri Group, the P. henselii Group, the P. gracilis Group and the P. olfersii Group. The P. gracilis Species Group was the same as that previously proposed by Nascimento et al. (2005). The P. henselii Group includes P. fernandezae and P. henselii, and was the sister group of a clade that comprised the remaining species of the P. cuvieri Clade. The P. olfersii Group included P. olfersii, P. soaresi, P. maximus, P. feioi and P. lateristriga. The P. biligonigerus Species Group was composed of P. biligonigerus, P. marmoratus, P. santafecinus and P. riograndensis. The P. cuvieri Group inferred here differed from that recognized by Nascimento et al. (2005) only by the inclusion of P. albifrons and the exclusion of P. cicada. The paraphyly of P. cuvieri with respect to P. ephippifer was inferred in all the analyses. Distinct genetic lineages were recognized among individuals currently identified as P. cuvieri and they were congruent with cytogenetic differences reported previously, supporting the hypothesis of occurrence of formally unnamed species. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Phylogeny; Systematics; Anura; Physalaemus